Cyclotides Isolated From Violet Plants of Cameroon Are Inhibitors of Human Prolyl Oligopeptidase - Gattringer, Jasmin; Ndogo, Olivier Eteme; Retzl, Bernhard; Ebermann, Carina; Gruber, Christian W.; Hellinger, Roland (Frontiers in Pharmacology, 2021)
Traditional medicine and the use of herbal remedies are well established in the African health care system. For instance, Violaceae plants are used for antimicrobial or anti-inflammatory applications in folk medicine. This study describes the phytochemical analysis and bioactivity screening of four species of the violet tribe Allexis found in Cameroon. Allexis cauliflora, Allexis obonensis, Allexis batangae and Allexis zygomorpha were evaluated for the expression of circular peptides (cyclotides) by mass spectrometry. The unique cyclic cystine-rich motif was identified in several peptides of all four species. Knowing that members of this peptide family are protease inhibitors, the plant extracts were evaluated for the inhibition of human prolyl oligopeptidase (POP). Since all four species inhibited POP activity, a bioactivity-guided fraction approach was performed to isolate peptide inhibitors. These novel cyclotides, alca 1 and alca 2 exhibited IC50 values of 8.5 and 4.4 µM, respectively. To obtain their amino acid sequence information, combinatorial enzymatic proteolysis was performed. The proteolytic fragments were evaluated in MS/MS fragmentation experiments and the full-length amino acid sequences were obtained by de novo annotation of fragment ions. In summary, this study identified inhibitors of the human protease POP, which is a drug target for inflammatory or neurodegenerative disorders.